Adolescents' behavioral and neural responses to e‐cigarette advertising. (11th April 2017) - Chen, Yvonnes; Fowler, Carina H.; Papa, Vlad B.; Lepping, Rebecca J.; Brucks, Morgan G.; Fox, Andrew T.; Martin, Laura E.
Abstract: Although adolescents are a group heavily targeted by the e‐cigarette industry, research in cue‐reactivity has not previously examined adolescents' behavioral and neural responses to e‐cigarette advertising. This study addressed this gap through two experiments. In Experiment One, adult traditional cigarette smokers ( n  = 41) and non‐smokers ( n  = 41) answered questions about e‐cigarette and neutral advertising images. The 40 e‐cigarette advertising images that most increased desire to use the product were matched to 40 neutral advertising images with similar content. In Experiment Two, the 80 advertising images selected in Experiment One were presented to adolescents ( n  = 30) during an functional magnetic resonance imaging brain scan. There was a range of traditional cigarette smoking across the sample with some adolescents engaging in daily smoking and others who had never smoked. Adolescents self‐reported that viewing the e‐cigarette advertising images increased their desire to smoke. Additionally, all participants regardless of smoking statuses showed significantly greater brain activation to e‐cigarette advertisements in areas associated with cognitive control (left middle frontal gyrus), reward (right medial frontal gyrus), visual processing/attention (left lingual gyrus/fusiform gyrus, right inferior parietal lobule, left posterior cingulate, left angular gyrus) and memory (right parahippocampus, left insula). Further, an exploratory analysis showed that compared with age‐matched non‐smokers ( n  = 7), adolescent smokers ( n  = 7) displayed significantly greater neural activation to e‐cigarette advertising images in the left inferior temporal gyrus/fusiform gyrus, compared with their responses to neutral advertising images. Overall, participants' brain responses to e‐cigarette advertisements suggest a need to further investigate the long‐run impact of e‐cigarette advertising on adolescents. Abstract : Adolescents ( n  = 30) with various smoking experiences (non‐smokers to daily smokers) self‐reported that viewing the e‐cigarette advertisements increased their desire to smoke. They also showed significantly greater brain activation to e‐cigarette advertisements in areas associated with cognitive control, reward, visual processing/attention, and memory. Further, an exploratory analysis showed that compared to age‐matched non‐smokers ( n  = 7), adolescent smokers ( n  = 7) displayed significantly greater neural activation to e‐cigarette advertising images in the left inferior temporal gyrus/fusiform gyrus, compared to their responses to neutral advertising images.